Gerenciamento do ciclo de aquisição de materiais na produção de edifícios - Ribeiro, Patrícia Keila Poepcke (2006)
The supply chain management can be considered as an expanded and updated vision of the traditional material s management. It is essential part of the quality of the construction, representing the integrated control and the global knowledge of the several existent flows in the production process. It is necessary to recognize that the supply sector constitutes substantial contribution for the company s operation. Among its several activities, the purchase of materials deserves an emphasis. It is verified that the necessary information and authorizations to manage this process flows thru several administrative sectors of the construction company. As strategy, companies use information and production planning and control systems integrated through computer software. Another used strategy is the practices of partnerships with the suppliers. However, it is verified that not always these strategies are implemented with success. In this context, it is the objective of this assignment to characterize the cycle of material purchase and its administration form in the construction of buildings. Through the method of case study two medium size construction companies were researched. The analyses allow to present guidelines that aid in the administration of the material purchase cycle.